Role of scientific correspondent points in railway science in 1942–1945 - I. A. Anokhov (Вестник Научно-исследовательского института железнодорожного транспорта, 2025)
Introduction. During the war, the country’s railway institutions faced the task to reorganise their work into a mobilisation mode as soon as possible. It became clear almost immediately that in new conditions, the functioning of several narrowly focused institutes was not advisable, and therefore, at the end of 1941, all the branch institutes of the People’s Commissariat of Communication Routes of the Soviet Union were merged into the All-Union Scientific Research Institute of Railway Transport. The rapidly changing situation in the field of transportation required science not only to make operational and practical decisions, but also to take additional steps to move scientific activities to the frontline zone. In this regard, the management of the Institute decided to create a network of scientif ic correspondent points.Materials and methods. Publications in the Railway Engineering journal for the period of 1942–1945, as well as archival materials of the Institute, were used in the article.Results. The role of scientific correspondent points in the restoration of communication routes during the war is highlighted. It is stated that the network of scientific correspondent points has become an effective organisational form for conducting applied research in environment close to military. This step resulted in a number of studies and developments that facilitated the operation of railway transport in the emergency conditions of that time.Discussion and conclusion. The materials of the article may be useful both for scientists and researchers studying the railway industry, as well as for industry heads. In addition, it may appeal to railway historians who seek to deepen their knowledge of the formation and development of this field.